Pengaruh Pemberian Infusa Herba Sambiloto (Andrographis paniculata Nees) Terhadap Glibenklamid Dalam Menurunkan Kadar Glukosa Darah Tikus Putih Jantan yang Dibuat Diabetes - Sari, Santi Purna; Azizahwati, Azizahwati; Ratimanjari, Diandra Andina (Majalah Ilmu Kefarmasian, 2012)
Many diabetics perform self-medication with antidiabetic herbs and synthetic drugs with the aim to obtain a synergistic or additive effects without informing their primary physician, such as the use of creat and glibenclamide. This research was carried out to know the impact of creat herb infusion on glibenclamide in bwering blood glucose levels on diabetic male albino rats. This study used 24 male Sparague-Lawley rats, which are divided into 6 groups, normal control and diabetic control were given 0,5% CMC solution I ml/200 g bw of rat, glibenclamide control were given glibenclamide suspension 0,9 mg/200 g bw of rat, creat control were given creat herb infusion 50 mg/200 g bw of rat, and 2 interaction groups were given creat herb infusion in 2 variant doses (50 and 100 mg/ 200 g bw of rat) and glibenclamide suspension 0,9 mg/200 g bw of rat, each of them were administrated orally. All of groups were induced with alloxan 32 mg/ 200 g bw of rat except normal control. Blood glucose was measured by 0-toluidine method at 2 hours and 4 hours after administration. The result showed that the creat herb infusion at 100 mg/200 g bw gave significant impact on glibenclamide in lowering blood glucose levels week after administration.